Freshwater fishes from Paraná State, Brazil: an annotated list, with comments on biogeographic patterns, threats, and future perspectives - Dos Reis, Renan Borges; Frota, Augusto; de Carvalho Deprá, Gabriel; Ota, Renata Rúbia; Da Graça, Weferson Júnio (Zootaxa, 2020)
An annotated checklist for the freshwater fishes from Paraná State, Brazil is provided. A total of 440 freshwater fish species are recorded for the state, distributed across five ecoregions: Upper Parana, Lower Parana, and Iguassu, all within the rio Paraná basin, and corresponding to the state’s Inland Slope, and Southeastern Mata Atlantica and Ribeira de Iguape, corresponding to the Atlantic Slope, encompassing minor coastal drainages emptying in the Baía de Paranaguá or in the Baía de Guaratuba, and the rio Ribeira de Iguape basin, respectively. The Upper Parana ecoregion ocuppies the larger in area in the state, and is divided into the following sub-ecoregions: Floodplain, Paranapanema, Piquiri, and Ivaí. Species richness for each ecoregion is as follows: 273 species for the Upper Parana (Paranapanema sub-ecoregion, 217 species; Floodplain sub-ecoregion, 193 species; Piquiri sub-ecoregion, 154 species; Ivaí sub-ecoregion, 132 species), 154 species in the Lower Parana, 127 species in the Iguassu, 68 species in the Southeastern Mata Atlantica, and 50 species in the Ribeira de Iguape. We recorded 42 putatively undescribed species and 117 endemic species from specific ecoregions (except Upper Parana) or sub-ecoregions in the state. Ninety-eight species recorded are non-native from at least one of the state’s ecoregions. Thirty-three species are considered threatened. The ecoregions in the Atlantic Slope share many more species with each other than with ecoregions in the Inland Slope. The Iguassu ecoregion is the only one located in Inland Slope that shares more species with the Atlantic Slope than with the remaining ecoregions from the Inland Slope. The Ivaí sub-ecoregion lacks several species that are common to all other sub-ecoregions of the Upper Parana ecoregion. Comments on the historical development of taxonomic knowledge, biogeography, threats, and conservation strategies for the fish fauna from the Paraná State are provided.